Free indirect discourse: an insurmountable challenge for literary MT systems? - Taivalkoski-Shilov Kristiina (My University, 2022)
This paper argues that an essential element affecting literary translation – the structure of narrative discourse – has been overlooked in research on literary MT systems so far. After abrief survey of basic concepts of structuralist narratology (Genette 1972), which are necessary for understanding essential aspects of literary translation, a type of reported speech called free indirect discourse is taken as an example of the translation problems which successful literary MT systems would have to tackle.
The Qualities of Literary Machine Translation